Campus Canopy, 1942-10-16 - The Campus Canopy, The Georgia State Woman's College (Georgia State Womans College, 1942)
Walter Shaw Will Play With Mario Braggiotti In Duo Concert Tonight -- GSWC In Units Least Affected By Enrollment Drop -- Nabokov Speaks At Meeting Of Clubs -- Versatile Mr. Nabokov Speaks of Writing and Science and Politics -- Seniors Arrange Gala Show and Carnival To Buy Bonds
Georgia State Womans College Student Newspaper
Keywords: Valdosta State University -- Periodicals